Minimal requirements for the human immunodeficiency virus type 1 V3 domain to support the syncytium-inducing phenotype: analysis by single amino acid substitution. - De Jong, J J (1992)
The third variable domain (V3) of the human immunodeficiency virus type 1 external envelope contains determinants of cell tropism, cytopathicity, and infectivity and elicits antibodies able to block infectivity in vitro and in vivo. Our study encompassed point-mutational analysis of HXB-2 viruses containing patient-derived V3 regions and expressing a non-syncytium-inducing, low-replicating phenotype in T-cell line SupT1. The mutation within V3 of a serine at position 306 into an also naturally occurring arginine (S to R) required an additional, naturally occurring mutation at position 320 (aspartate to glutamine, D to Q) or 324 (aspartate to asparagine, D to N) for full expression of the syncytium-inducing, high-replicating (SI) phenotype. The naturally occurring mutation of an aspartate into an arginine at position 320 (D to R) was sufficient for production of the SI phenotype. This study proves that introduction of a positively charged amino acid at position 306 or 320, previously shown to be strongly associated with the SI phenotype in field isolates (R.A.M. Fouchier, M. Groenink, N.A. Kootstra, M. Tersmette, H.G. Huisman, F. Miedema, and H. Schuitemaker, J. Virol. 66:3183-3187, 1992), is minimally required for production of SI viruses. In addition, naturally occurring mutations at residue 324 also modulate the virus phenotype.